New delay-dependent robust stability criterion for neutral stochastic neural networks with time delays - Qiu-Ji Qing; Hai-Kuo He; Duo-Ming Xi; Ji-Yong Lu (2009 International Conference on Machine Learning and Cybernetics, 2009)
In this paper, the problem of delay-dependent robust stability for uncertain neutral stochastic neural networks with time delays is considered. Based on Lyapunov stability theory combined with linear matrix inequalities (LMIs) techniques, some new delay-dependent stability conditions in terms of LMIs are derived by introducing some free weighting matrices and using Leibniz-Newton formula which can be selected properly to lead to less conservative results. Finally, a numerical example is given to illustrate the feasibility and effectiveness of the results.